Trypanosome diversity in wildlife species from the serengeti and Luangwa Valley ecosystems. - Harriet Auty; Neil E Anderson; Kim Picozzi; Tiziana Lembo; Joseph Mubanga; Richard Hoare; Robert D Fyumagwa; Barbara Mable; Louise Hamill; Sarah Cleaveland; Susan C Welburn (Public Library of Science (PLoS), 2012)
BACKGROUND: The importance of wildlife as reservoirs of African trypanosomes pathogenic to man and livestock is well recognised. While new species of trypanosomes and their variants have been identified in tsetse populations, our knowledge of trypanosome species that are circulating in wildlife populations and their genetic diversity is limited. METHODOLOGY/PRINCIPAL FINDINGS: molecular phylogenetic methods were used to examine the genetic diversity and species composition of trypanosomes circulating in wildlife from two ecosystems that exhibit high host species diversity: the Serengeti in Tanzania and the Luangwa Valley in Zambia. Phylogenetic relationships were assessed by alignment of partial 18S, 5.8S and 28S trypanosomal nuclear ribosomal DNA array sequences within the Trypanosomatidae and using ITS1, 5.8S and ITS2 for more detailed analysis of the T. vivax clade. In addition to Trypanosoma brucei, T. congolense, T. simiae, T. simiae (Tsavo), T. godfreyi and T. theileri, three variants of T. vivax were identified from three different wildlife species within one ecosystem, including sequences from trypanosomes from a giraffe and a waterbuck that differed from all published sequences and from each other, and did not amplify with conventional primers for T. vivax. CONCLUSIONS/SIGNIFICANCE: Wildlife carries a wide range of trypanosome species. The failure of the diverse T. vivax in this study to amplify with conventional primers suggests that T. vivax may have been under-diagnosed in Tanzania. Since conventional species-specific primers may not amplify all trypanosomes of interest, the use of ITS PCR primers followed by sequencing is a valuable approach to investigate diversity of trypanosome infections in wildlife; amplification of sequences outside the T. brucei clade raises concerns regarding ITS primer specificity for wildlife samples if sequence confirmation is not also undertaken.